PENGARUH GELLING AGENT PADA SEDIAAN SERUM JERAWAT KOMBINASI EKSTRAK DAUN SIRIH HIJAU DAN BUAH BELIMBING WULUH - Dara Tilarso (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2022)
Abstract Serums with low viscosity can deliver active substances through the skin surface by forming a film layer. The physical properties of a good serum depend on the use of a gelling agent as a base. This study aims to determine the effect of the type and concentration of gelling agent on the physical characteristics of the combination of ethanol extract of green betel leaf (Piper betle) and wuluh starfruit (Averrhoa bilimbi L.) as an anti-acne. Serum preparations were made in 6 formulas with variations and concentrations of gel base, namely FI (Na-CMC 2%), FII (Na-CMC 3%), FIII (Na-CMC 4%), FIV (Carbopol 0.5%), FV (Carbopol 1%), and FVI (Carbopol 2%). Evaluation of the preparation is carried out to determine the optimum formula that meets the requirements criteria. The evaluations carried out included organoleptic homogeneity, dispersion, adhesion, pH, and viscosity. The analysis performed statistically using ANOVA with a 95% confidence level to see differences between groups of formulas to determine the effect of type and concentration of gelling agent on serum characteristics. The formulation of serum preparations on the concentration of gelling agent affects the physical stability for 28 days. The results of the antibacterial activity test of FV and FVI (Karbopol 1% and 2%) had inhibition zones of 8.8 mm and 9.3 mm in P. acnes, and 9 and 9.8 mm in S. aureus which were included in the inhibition zone category currently.